Odpowiedź :
Odpowiedź:
8(3x-12)=24x-96
-5(-6x+3y-1)=+30x-15y+5
2x(9x-12)=18x2-24x
(24x-10y+32):2=12x-5y+16
(21x2-70x+49):(-7)=-3x2+10x-7
3(9x-10y)+5(2x-6y)=27x-30y+10x-30y=37x-60y
-6(-5x+7)-(4x-12)+(7z+11)=30x-42-4x+12+7z+11=26x-19+7z
Szczegółowe wyjaśnienie:
Odpowiedź:
[tex]a)8(3x - 12) = 24x - 96 \\ b) - 5( - 6x + 3y - 1) = 30x - 15y + 5 \\ c)2x(9x - 12) = 18 {x}^{2} - 24x \\ d)(24x - 10y + 32) \div 2 = 12x - 5y + 6 \\ e)(21 {x}^{2} - 70x + 49) \div ( - 7) = - 3 {x}^{2} + 10x - 7[/tex]
[tex]f)3(9x - 10y) + 5(2x - 6y) = 27x - 30y + 10x - 30y = 17x - 60y[/tex]
[tex]g) - 6( - 5x + 7) - (4x - 12) +( 7z + 11) = 30x - 42 - 4x + 12 + 7z + 11 = 26x + 7z - 19[/tex]